A descriptive analysis of emergency medicine resident productivity over the course of training. (29th September 2021) - Fredette, Jenna; Kim, Tae; McHugh, Daniel; Gissendaner, Jamie; Cherico, Amy; Mapp, Alexandra; Brennan, Daniel; Thundiyil, Josef; Nomura, Jason
Abstract: Background: The primary objective of emergency medicine (EM) residency training is to develop knowledgeable, procedurally competent, and highly efficient physicians. We aimed to determine current overall productivity statistics and if there is an average rate of productivity change for individual residents as they progress through their training. Methods: This was a retrospective review of EM resident productivity performed at two American Council of Graduate Medical Education–accredited, community‐academic residency programs from July 2012 to June 2018. Productivity was defined by relative value units (RVU)/h, RVU/patient, and patients/h. Mixed‐effects models for repeated‐measures data were used to assess change in outcome over postgraduate year (PGY) levels. The models included the interaction between progressive PGY levels to assess whether there was a pattern of change between each training year. Results: A total of 102 unique EM residents were included in the analysis. All three productivity measures increased linearly between PGY levels. However, while each graduating class had linear improvement throughout training, the rates of change were not consistent from one class to the next. Furthermore, a consistent rate of change between PGY for individual residents could not be established. Productivity can increase, decrease, stay the same, or any combination as residents advance through their training. Conclusions: Overall productivity of EM residents increases as they advance through their training. However, there is no consistent pattern of increase from one graduating class to the next and no reliable pattern of change for individual residents. Having increased granularity and understanding of productivity as it relates to individual residents will allow for more enhanced advisement of residents about their current productivity and their anticipated course through residency.